Influence of Water Stress on Canopy Temperature and Yield Contributing Characteristics of Wet Seeded Rice - Parveen, S; Humphreys, E (Bangladesh Rice Journal, 2023)
Canopy temperature (CT) is one of the indices for evaluating water stress. The study has been taken to correlate water stress with CT and to evaluate effect of water stress on crop and yield performance of wet seeded rice (WSR). The canopy temperature of rice at vegetative and flowering stages were investigated under different soil water stresses. The field experiment was conducted at IRRI (International Rice Research Institute) during dry season, 2011. Three levels of water stress (-10, -20 and -40 kPa) were applied at 3-leaf (3L) to panicle initiation (PI), PI to flowering (FL) and FL to physiological maturity (PM) stages. One non -stressed treatment, i.e., continuously flooded puddled transplanted rice (PTR-CF) was used as a control. Soil water tension was measured using a 30-cm long gauge tensiometer and a handheld infrared thermometer was used to measure CT. Canopy temperatures were recorded from 3L to PI and PI to FL stages. In both the stages, CT was within the range of marginal stress. Canopy temperature depression (CTD) was higher in the stressed condition than that of the nonstressed. At the PI stage, leaf area index (LAI) was significantly lower in WSR than PTR -CF. LAI was comparatively lower in WSR with -20 kPa and -40 kPa than WSR with -10 kPa and PTR-CF when water stress imposed during PI-FL. Decreasing grain yield was observed when irrigation threshold increased from -10 to -40 kPa during PI to FL and FL to PM, but the differences were not significant. Yield components of WSR with different stresses were not significantly different. But spikelet fertility (%) and grain weight (g) of WSR was significantly higher than that of PTR-CF. The yield of PTR-CF was similar to the yield of WSR. Panicle/m2 correlated negatively with CT under a stressed condition. Yield and all yield components ex cept spikelet per panicle were positively correlated with CT at 60 days after seeding (CT 60). Under stressed condition, CT correlated negatively with the grain yield. Results revealed that CT correlated positively with grain yield under non-stressed condition (CT35 and CT60). Spikelet fertility percentage (SF%) correlated negatively with CT35 and CT46. It has been concluded that CT and CTD may be used for water stress evaluation. Bangladesh Rice J. 25 (2) : 69-76, 2021